Peningkatan Mutu Buah Jeruk Siem Berdasarkan Masa Panen Basis Kalender dan Karakteristik Fisik dan Sensorisnya - Handayani, Nurma; Akhiriani, Shanti; Rahmawati, Ani (JURNAL AGROTEKNOLOGI, 2023)
Harvesting the siem orange from its plants usually is not uniform. Citrus farmers sell their crops based on the request of the middlemen regardless of the age of harvest. Thus the price is relatively cheaper because it depends on the middleman during selling. So, this research aims to improve the quality of siem orange fruit based on the calendar harvesting and physical sensory characteristics. These research was conducted on farmers in Krai Village, Yosowilangun District, Lumajang Regency during the harvest period from March to July 2023. The flowering period for siem oranges was calculated at least 40 weeks in advance. Parameters observed in this study included diameter and weight, degrees of brix, sensory to grain color/squeeze, and level of sweetness. The results showed that the good quality of siem oranges fruits were produced in the harvest calendar from 32 to 36 weeks after flowering. Meanwhile for orange squeeze drink, siem orange harvested at 29 weeks after flowering. Good quality of siem oranges had a heavy weight of siem orange, juicy, dark orange pulp color, and brix degree value ranging of 10–12o. Based on this study, it was recommended for farmers to harvest siem oranges at the optimal harvesting age of 34 weeks from the flowering period so that the quality of the siem oranges fruits was optimal and the selling price could be higher. Keywords: brix value, grade, quality, siem orange fruit